Efficacy of Indirect Decompression by Posterior Longitudinal Ligament Ligamentotaxis in Minimally Invasive Oblique Lateral Interbody Fusion (MIS-OLIF) Without Posterior Decompression for Degenerative Lumbar Disease - Jung-Woo Hur; Dong Hun Kim; Seonyong Yun; Jae Taek Hong (Journal of Clinical Medicine, 2026)
Background/Objectives: Indirect decompression through restoration of disc and foraminal height with a large lateral interbody cage has been advocated for selected patients, but its efficacy in a large series remains unproven. In this retrospective study, we evaluated the clinical and radiographic results of indirect decompression achieved by posterior longitudinal ligament (PLL) ligamentotaxis in minimally invasive oblique lateral interbody fusion (MIS-OLIF) performed without posterior decompression. Methods: We retrospectively reviewed 236 consecutive patients treated for single- or two-level degenerative lumbar disease (November 2019–May 2025); clinical follow-up of at least 24 months was available in 181 patients. Visual analogue scale (VAS) scores and radiographic parameters—disc height, foraminal height, foraminal area, spinal canal diameter and cross-sectional area (CSA) of the thecal sac—were compared before and after surgery, and extension ratios were correlated with preoperative values. Results: Clinical scores improved significantly. All radiographic parameters increased substantially: disc height +49.1%, foraminal height +33.7%, foraminal area +44.5%, canal diameter +37.4% and CSA +36.2%. Extension ratios were inversely correlated with preoperative values. Six patients (2.5%) required additional posterior decompression. The slippage subgroup showed greater radiographic gains than the stenosis subgroup. Conclusions: MIS-OLIF without posterior decompression significantly enlarged the foramen and spinal canal; reduction in disc bulging and PLL ligamentotaxis may contribute to this effect, with greater improvement in more severely degenerated, overtly slipped segments. Careful patient selection remains essential, and prospective comparative studies with longer follow-up are needed.